JavaFX 9 by example : rich-client applications for any platform - Dea, Carl (Apress, 2017)
Create media-rich client applications using JavaFX 9 and the Java 9 platform. Learn to create GUI-based applications for mobile devices, desktop PCs, and even the web. Incorporate media such as audio and video into your applications. Interface with hardware devices such as Arduino and Leap Motion. Respond to gesture control through devices such as the Leap Motion Controller. Take advantage of the new HTTP2 API to make RESTful web requests and WebSockets calls. New to this edition are examples of creating stylized text and loading custom fonts, guidance for working with Scene Builder to create visual layouts, and new content on developing iOS and Android applications using Gluon mobile. The book also covers advanced topics such as custom controls, JavaFX 3D, gesture devices, printing, and animation. Best of all, the book is full of working code that you can adapt and extend to all your future projects. Is your goal to develop visually exciting applications in the Java language? Then this is the book you want at your side. JavaFX 9 by Example is chock-full of engaging, fun-to-work examples that bring you up to speed on the major facets of JavaFX 9. You'll learn to create applications that look good, are fun to use, and that take advantage of the medium to present data of all types in ways that engage the user and lead to increased productivity. The book: Has been updated with new content on modular development, new APIs, and an example using the Scene Builder tool Is filled with fun and practical code examples that you can modify and drop into your own projects Includes an example using Arduino and an accelerometer sensor to track motion in 3D Helps you create JavaFX applications for iOS and Android devices What You'll Learn: Work with touch-based interfaces Interpret gesture-based events Use shapes, color, text, and UI controls animation to create a si mple click and point game Add audio and video to your projects Utilize JavaFX 3D Create custom controls using CSS, SVG, and Canvas APIs Organize code into modules using Java Platform Module System (Project Jigsaw).